Kekuatan Hukum MoU Dari Segi Hukum Perjanjian - Sopamena, Ronald Fadly (Faculty of Law, Universitas Pattimura, 2021)
Prior to a business transaction, initial negotiations are usually carried out. Negotiation is a process of trying to reach an agreement with other parties. Negotiation is also an instrument that bridges the various interests of business actors in formulating their rights and obligations. It is in this negotiation that the bargaining process takes place. The next stage is the making of a memorandum of understanding, which in this writing is abbreviated as MoU. This study aims to examine whether the MoU can be used as a preliminary agreement as well as the legal strength of the MoU in terms of contract law. This research methodology uses normative legal tracing, primary and secondary legal materials with a statutory approach and a conceptual approach. Based on the research results, in a business contract, the negotiations carried out by the parties are outlined in the MoU as the initial agreement. If in the preliminary agreement stage there is a cancellation unilaterally, then as a legal consequence, the party making the cancellation must be responsible for the losses incurred. This form of responsibility is in the form of refunding costs incurred during negotiations and compensation for lost opportunities to enter into contracts with third parties.